Menjaga Korelasi Pemahaman Konseptual Model Pembelajaran Berbasis Proyek dengan Kemampuan Kewirausahaan - Suprapta Suprapta; Sulaiman Siddiq (Seminar Nasional LP2M UNM, 2019)
Activities that are repeated will continue to change people into experts. This simple understanding is the basis of this research. Independence is formed is a habit that is embedded in entrepreneurial practice that starts from the plan, implementation and evaluation and produce something according to purpose. The aim of this study is to reveal the level of conceptual understanding of project-based learning models, Geography students who have passed the Entrepreneurship course. Is there a correlation between the ability of conceptual understanding of project-based learning models with Entrepreneurship Capabilities. The most important entrepreneurship subject is forming independent students. Students do not just rely on their ability to become civil servants or employees. Students equipped with entrepreneurial knowledge are expected to be independent and can open their own jobs. The picture of independence will imprint on every student and one of the logical understandings is that independence is manifested in everythink activity in life. The value of the ability to master the conceptual model of project-based learning achieves good categorization and the value of the ability of students to master entrepreneurship is very good. The two variables are not correlated because students are not accustomed to making learning plans with project-based learning models and inspiring entrepreneurial projects that doit’s.